2010
DOI: 10.1289/ehp.0901205
|View full text |Cite
|
Sign up to set email alerts
|

Probabilistic Modeling of Dietary Arsenic Exposure and Dose and Evaluation with 2003–2004 NHANES Data

Abstract: BackgroundDietary exposure from food to toxic inorganic arsenic (iAs) in the general U.S. population has not been well studied.ObjectivesThe goal of this research was to quantify dietary As exposure and analyze the major contributors to total As (tAs) and iAs. Another objective was to compare model predictions with observed data.MethodsProbabilistic exposure modeling for dietary As was conducted with the Stochastic Human Exposure and Dose Simulation–Dietary (SHEDS-Dietary) model, based on data from the Nationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
124
4
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(138 citation statements)
references
References 25 publications
9
124
4
1
Order By: Relevance
“…e l s e v i e r . c o m / l o c a t e / f o o d c h e m t o x chromated copper arsenate -treated wood (Meacher et al, 2002;Schoof et al, 1999;Tsuji et al, 2007;Xue et al, 2010;Yost et al, 2004). Contaminated drinking water is the largest source of exposure to As in regions where contamination is a problem even at moderate levels (Meliker et al, 2006), whereas rice is the largest iAs source in regions where drinking water As exposure is low (Fontcuberta et al, 2011;Meacher et al, 2002;Meliker et al, 2006;Tsuji et al, 2007;Xue et al, 2010).…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
See 1 more Smart Citation
“…e l s e v i e r . c o m / l o c a t e / f o o d c h e m t o x chromated copper arsenate -treated wood (Meacher et al, 2002;Schoof et al, 1999;Tsuji et al, 2007;Xue et al, 2010;Yost et al, 2004). Contaminated drinking water is the largest source of exposure to As in regions where contamination is a problem even at moderate levels (Meliker et al, 2006), whereas rice is the largest iAs source in regions where drinking water As exposure is low (Fontcuberta et al, 2011;Meacher et al, 2002;Meliker et al, 2006;Tsuji et al, 2007;Xue et al, 2010).…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
“…Studies have been pointing out the role of rice in people's exposure to arsenic (Meacher et al, 2002;Meharg et al, 2009;Meliker et al, 2006;Schoof et al, 1999;Sun et al, 2008;Tsuji et al, 2007;Williams et al, 2007b;Xue et al, 2010;Yost et al, 2004;Zhu et al, 2008), and consumer groups have been calling for a Maximum Contaminant Level (MCL) (Jalonick, 2012). While no MCL is in place in the US and the EU, China promulgates an MCL of 150 ng/g for iAs (Qian et al, 2010), and Hungary and China have 300 ng/g and 700 ng/g, respectively for tAs (Mihucz et al, 2007;Qian et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The principal exposures routes for As are via drinking water, foods and inhaled particulates (Mondal et al, 2010), with many studies detailing the importance of the food pathway to overall As body burdens (Georgopoulos et al, 2007;Meacher et al, 2002;Mondal et al, 2010;Schoof et al, 1999;Xue et al, 2010). In West Bengal (India) it has been shown that even for populations exposed to high As levels in the drinking water, rice constitutes a major source of iAs in the diet (Mondal and Polya, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…This finding suggests that incorporating water consumption may improve prediction of arsenic in urine. Likewise, intake of water, beverages or foods made with tap water, or the consumption of other foods, such as fish, also influence arsenic exposure (Xue et al, 2010) and the amount of arsenic excreted in urine.…”
Section: Introductionmentioning
confidence: 99%